Eski Türklerin Savaş Taktikleri ve Savaş Alanındaki Uygulamaları - Eda DURMUŞ (Gazi Akademik Bakış)
The steppe, where a great part of the Turkic population has been lived, influenced deeply their social, political, religious, judicial and military features. Especially their weaponry can be observed in these terms. The main factor of the old Turkic warfare was the horse. Turkic military tactics were shaped around the very speed and manoeuvre capabilities of the horse. Distant warfare based on using bows on the horse helped them to lessen their losses. The classical Turkic tactic known as the Turan tactic or the wolf game realised in three phases: The first phase contains intimidation and attrition. This act aimed at weakening the enemy and they did not hope eventual consequences after that. The second phase is the false retreat. The attackers started to withdraw as if they were defeated; the enemy became surprised and was taken to the field where the attackers had planned to wage the war. The third part of the tactic was to ambush and destroy the enemy. Since the tired enemy came where the attackers had made their preparations, it was not difficult to hit a fatal impact and to win the war. The three factors enabling to use this tactic efficiently were human source, geographical environment and timing. The performer of the strategy is the human-being. The lifestyle of the ancient Turks paved the way to produce able warriors. Indeed, their daily activities were all concerning with military preparations in a sense. Therefore, they were very familiar of the tactics, acts and conditions of the war, which helped also to increase their self-confidence and bravery. Another factor in terms of war strategies is the geographical settings. The effective use of the horse in the steppe led to shape the principal military strategies. Since the armies of the steppe peoples were composed of cavalry troops, they needed the lands suitable to ride speedily and to make manoeuvres easily. It was also very vital to easily access on the horse to the ambush places, usually passes and valleys. The army had to deal with the enemy on a suitable place, but also as mounted. Success was depended on providing those conditions. Controlling the strategical points was conditional for the mounted troop to have upper hand before the enemy. Thus, it became essential in exerting the tactic. They had to know not only when and where, but also how to attack on the enemy. If the estimations promise for a success, then they would start the action. If not, they used to cancel the assault. Scythians, Huns, Kök Türks and the succeeding Turkic peoples applied this strategy very well.